Penggunaan Smartphone Application Guna Mempelajari Cara Mengurus Jenazah Umat Muslim - Wiedanto Prasetyo, Muhamad Awiet; Karini, Zulia; Ayubi, Harun Al (Politeknik Negeri Ujung Pandang, 2019)
The obligation of Muslim towards their relatives who died there are four cases, namely bathing, believing, praying and burying. The community considers that there is no need to think about how to care for the body from the beginning to the finish because there are already their own officers. Rhile in a hadist from ‘Aisyah said Rasullah SAW: “Anyone who bathes a corpse and is guarded by trust and cannot be opened (secret) about the protection of the sympathy for the people there hen comes from sin for hs condition. Based on the hadist mentioned the person who mentioned bathe the corpse in priority is his own closest family, then if the family cannot, then other people can do it, while bathing is included in the case of receiving a corpse based on the results of an interview with teacher Madrasah Diniyah Baitul Athfal by agreeing to him about the management of the body, it is expected if it involves family members. Who can use the world od the sunna of the prophet and also in the future can be used as a successor. In Madrasah Diniyah Baitul Athfal involved in the learning process due to shortages in madrasah are short plus students do not have books about the management of bodies or jurisprudence books become obstacles in the process of learning. Teaching lessons for students or instructors. After obtaining data from data collection, .researchers create a system with predetermined and more relevant methods using the Multimedia Development Life Cycle (MDLC) Method. Based on the results obtained for 9352 and included in the category of Good, then the application was validated that can be applied to the research object.